Legal Protection for Consumers Who Use Electronic Wallets (E-Wallets) As a Means of Payment - Asriati (Alauddin Law Development Journal (ALDEV), 2024)
This research aims to explore and analyze the legal protection of e-wallet applications as a means of payment, as well as factors that influence the use of e-wallets in transactions. The research method used is normative legal research, which relies on the analysis of library materials and secondary data, taking into account the suitability between the theory applied and the relevant legal aspects. The results of this study indicate that to achieve legal protection against e-wallet applications as a means of payment there are two significant things. The first is the legal protection given to customers in cases of data leakage, regulated in Law Number 8 Year 1999 concerning Consumer Protection. Second, the obligations of digital wallet service providers to customers related to financial losses are regulated in Article 7 Letter f of the Consumer Protection Law.